Behavioral and Anthropometric Predictors of Noncommunicable Diseases Among Older Adults: The Dominance of Smoking and Central Obesity - Dian Yuniar Syanti Rahayu; Supriadi Supriadi; Susi Susanti; Sugiyanto Sugiyanto (Direktorat Politeknik Kesehatan Makassar, 2026)
The escalating burden of Noncommunicable Diseases (NCDs) poses a significant public health challenge in low- and middle-income countries, including Indonesia. In the Rancakalong Health Center area, Sumedang, hypertension prevalence among older adults has reached a critical 56.8%. This study aimed to identify and delineate the risk profiles of community-based NCDs—specifically a reported history of hypertension, diabetes mellitus, or dyslipidemia—among the older population. A cross-sectional study was conducted using a total sampling technique, involving 711 older adults. Data were collected using the validated Modified NCD Screening Form, covering lifestyle parameters, anthropometry, and clinical history. Independent predictors were identified using multivariate logistic regression analysis. The prevalence of NCD history among subjects was 57.9%. The multivariate model identified smoking habits as the strongest predictor (OR=3.49; 95% CI: 2.35–5.18; p<0.001). Other significant risk factors included infrequent vegetable/fruit consumption (OR=1.79; p<0.001), high-salt/fat intake (OR=2.12; p<0.001), overweight and obesity (OR=1.82–3.00; p=0.003), and increased abdominal circumference (OR=2.46; p<0.001). Conversely, low to moderate physical activity showed a protective effect (OR: 0.58 and 0.40; p<0.001), while alcohol consumption was not statistically significant (p=0.823). These findings underscore the urgency of evidence-based public health interventions at the primary care level. Shifting the focus toward lifestyle modifications is essential to mitigate NCD risks and enhance the quality of life for older adults in community settings.